2014
DOI: 10.5935/0101-2800.20140070
|View full text |Cite
|
Sign up to set email alerts
|

Selenium plasma levels in hemodialysis patients: Comparison between North and Southeast of Brazil

Abstract: We concluded that patients from North (Amazon) region present higher plasma Se levels when compared to the patients from Southeast of Brazil. However, independently of the region, HD patients presented Se deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…Only 2.3% of HD patients had hyposeleniemia. Inconsistent with our findings, a study in Brazil found that all HD patients have Se deficiency [16]. The difference between the two studies may be related to differences in dietary intake of Se and Se concentration in soil.…”
Section: Discussioncontrasting
confidence: 50%
“…Only 2.3% of HD patients had hyposeleniemia. Inconsistent with our findings, a study in Brazil found that all HD patients have Se deficiency [16]. The difference between the two studies may be related to differences in dietary intake of Se and Se concentration in soil.…”
Section: Discussioncontrasting
confidence: 50%
“…[31][32][33] Although the reason for reduced erythrocyte and plasma Se levels in CRF patients is not completely explained, reduced dietary intake, impaired intestinal absorption, increased urinary loses and abnormal binding to Se transport proteins could be responsible for this phenomenon. 34,35 Decreased protein intake has been proposed as a significant cause of Se insufficiency, as protein foodstuffs contain the largest amount of Se. 9 The current investigation showed a significant decrease in plasma GPx activity in CRF patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…The low natural levels of Se in soils and its absence in fertilization to crops explain the low contents in food from vegetables [12] and consequently in Brazilian diet, except for northern areas [2]. Although, in a study of hemodialysis patients from north and southeast of Brazil, both patient groups presented low Se plasma levels when compared to recommended values; independently of the region, all patients presented Se deficiency [13].…”
Section: Selenium Fertilization In Tropical Weathered Soilsmentioning
confidence: 99%
“…According to the Selenium-Tellurium Development Association, the best way for Se application is along with other nutrients [15]. There are positive effects in Se application along with phosphorus fertilization [13].…”
Section: Selenium Fertilization In Tropical Weathered Soilsmentioning
confidence: 99%
See 1 more Smart Citation